Microfiltration of concentrated albumin solutions and the role of processing conditions on membrane fouling - Andrea Iginio Cirillo; Giovanna Tomaiuolo; Stefano Guido (Chemical Engineering Journal Advances, 2023)
Membrane processing is a subject of growing scientific and industrial interest as a valuable technology to replace conventional energy-intensive operations, but is hindered by the progressive decrease of permeate flux caused by membrane fouling. Although physico-chemical factors affecting membrane fouling have been widely investigated, less is known concerning the effects of processing conditions. Here, we focus on microfiltration of aqueous bovine serum albumin (BSA) solutions by using a novel miniaturized modular unit allowing to study both dead-end (DE) and crossflow (CF) filtration. Pure water flux measurements and Computational Fluid Dynamics (CFD) simulations were firstly performed to characterize the flow field inside the module. In presence of BSA, at the same transmembrane pressure (TMP) of 20 mbar and average pore size of 0.45 μm, a remarkable decrease in the fouling progression with time was found for CF with a peristaltic pump as compared to pressure-driven DE filtration. Furthermore, BSA concentration in the permeate was the same as in the feed for peristaltic CF, while negligible for DE. By either increasing transmembrane pressure or lowering membrane pore size, a stronger decay of permeate flux with time was observed. Scanning electron microscopy images of the membrane showed the presence of a thick surface cake layer under peristaltic CF, which became thinner by increasing TMP or reducing membrane pore size. Overall, the better performance of peristaltic CF can be interpreted in terms of reduced BSA residence time in the membrane, membrane deformability and formation of a permeable cake layer at lower TMP and larger membrane pore size. The innovative design of our filtration module and the combination of permeate flux and concentration measurements with CFD results and microscopy observations constitute the most significant aspects of this research work, which provides a multiscale picture of membrane fouling. The insight emerging from results aims to provide qualitative guidelines towards an optimal setting of processing conditions in membrane operations, which is highly needed to improve the membrane innovation pipeline.